Lack of association of the HMGA1 gene variants with insulin resistance risk development in the Iraqi population: Case-control study - Mirna Kifah Faiq; Eman Saadi Saleh; Omar Basher Fathalla (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Reduced sensitivity or responsiveness to the metabolic effects of insulin is the typical definition of insulin resistance. High mobility group A1 (HMGA1) can enhance the body's capacity to store fat and improve insulin sensitivity, so the abnormal decrease in HMGA1 or its variants may be related to type 2 diabetes and poor adipocyte differentiation, which results in insulin resistance. The goal of this study was to examine whether HMGA1 genetic variants in a sample of the Iraqi population can predict the risk of an increase in insulin resistance. This case-control study was carried out at a single center in Kirkuk, Iraq, from February to August 2022. This study included 30 healthy Iraqi participants and 30 patients without diabetes who had metabolic syndrome. Sanger sequencing of genomic DNA was used to identify HMGA1 polymorphisms and genotypes. The high prevalence of CC and GG genotypes of rs1023028442 and rs112081775 respectively was seen in the Iraqi population. Minor allele frequency of rs1023028442 was higher among metabolic patients without diabetes with (MAF=0.08) compared to the control group with (MAF= 0%). While (MAF=0.1) of rs112081775 was seen in metabolic patients without diabetes compared to (MAF=0.02) in the control group. After adjusting age, gender, and BMI as covariates, linear regression analysis showed no significant effect of these two variants (C>T, and G>A) on developing insulin resistance. Thus, the rs1023028442 with C>T genotype and rs112081775 with G>A genotype in the HMGA1 gene did not predict the risk of an increase in insulin resistance in the Iraqi populations.